Cardamine libagouensis, a new species from Hubei, China - Diao, Ying; Zhao, Chufeng; Chen, Yongbo; ZhongLi, Hu (Nordic journal of botany, 2023)
Cardamine libagouensis (Brassicaceae), a new species from Enshi City, Hubei, China, is described and illustrated. The new species is morphologically similar to C. engleriana, but differs by lacking stolons, basal leaves pinnate, sepals 1.0–1.5 mm long, silique 3–4 cm long, and seeds without wings. A preliminary molecular phylogenetic study based on ITS2 sequences suggests that C. libagouensis is closely related to C. engleriana and C. griffithii.